0=(5x-31)(x)-75

Simple and best practice solution for 0=(5x-31)(x)-75 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=(5x-31)(x)-75 equation:


Simplifying
0 = (5x + -31)(x) + -75

Reorder the terms:
0 = (-31 + 5x)(x) + -75

Reorder the terms for easier multiplication:
0 = x(-31 + 5x) + -75
0 = (-31 * x + 5x * x) + -75
0 = (-31x + 5x2) + -75

Reorder the terms:
0 = -75 + -31x + 5x2

Solving
0 = -75 + -31x + 5x2

Solving for variable 'x'.

Combine like terms: 0 + 75 = 75
75 + 31x + -5x2 = -75 + -31x + 5x2 + 75 + 31x + -5x2

Reorder the terms:
75 + 31x + -5x2 = -75 + 75 + -31x + 31x + 5x2 + -5x2

Combine like terms: -75 + 75 = 0
75 + 31x + -5x2 = 0 + -31x + 31x + 5x2 + -5x2
75 + 31x + -5x2 = -31x + 31x + 5x2 + -5x2

Combine like terms: -31x + 31x = 0
75 + 31x + -5x2 = 0 + 5x2 + -5x2
75 + 31x + -5x2 = 5x2 + -5x2

Combine like terms: 5x2 + -5x2 = 0
75 + 31x + -5x2 = 0

Begin completing the square.  Divide all terms by
-5 the coefficient of the squared term: 

Divide each side by '-5'.
-15 + -6.2x + x2 = 0

Move the constant term to the right:

Add '15' to each side of the equation.
-15 + -6.2x + 15 + x2 = 0 + 15

Reorder the terms:
-15 + 15 + -6.2x + x2 = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -6.2x + x2 = 0 + 15
-6.2x + x2 = 0 + 15

Combine like terms: 0 + 15 = 15
-6.2x + x2 = 15

The x term is -6.2x.  Take half its coefficient (-3.1).
Square it (9.61) and add it to both sides.

Add '9.61' to each side of the equation.
-6.2x + 9.61 + x2 = 15 + 9.61

Reorder the terms:
9.61 + -6.2x + x2 = 15 + 9.61

Combine like terms: 15 + 9.61 = 24.61
9.61 + -6.2x + x2 = 24.61

Factor a perfect square on the left side:
(x + -3.1)(x + -3.1) = 24.61

Calculate the square root of the right side: 4.960846702

Break this problem into two subproblems by setting 
(x + -3.1) equal to 4.960846702 and -4.960846702.

Subproblem 1

x + -3.1 = 4.960846702 Simplifying x + -3.1 = 4.960846702 Reorder the terms: -3.1 + x = 4.960846702 Solving -3.1 + x = 4.960846702 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.1' to each side of the equation. -3.1 + 3.1 + x = 4.960846702 + 3.1 Combine like terms: -3.1 + 3.1 = 0.0 0.0 + x = 4.960846702 + 3.1 x = 4.960846702 + 3.1 Combine like terms: 4.960846702 + 3.1 = 8.060846702 x = 8.060846702 Simplifying x = 8.060846702

Subproblem 2

x + -3.1 = -4.960846702 Simplifying x + -3.1 = -4.960846702 Reorder the terms: -3.1 + x = -4.960846702 Solving -3.1 + x = -4.960846702 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.1' to each side of the equation. -3.1 + 3.1 + x = -4.960846702 + 3.1 Combine like terms: -3.1 + 3.1 = 0.0 0.0 + x = -4.960846702 + 3.1 x = -4.960846702 + 3.1 Combine like terms: -4.960846702 + 3.1 = -1.860846702 x = -1.860846702 Simplifying x = -1.860846702

Solution

The solution to the problem is based on the solutions from the subproblems. x = {8.060846702, -1.860846702}

See similar equations:

| -2.8y=3.08 | | 10+25x=5(5x+3) | | 3128=34.08x | | ln(x-5)=lnx-ln*5 | | 24x+6= | | 3128=34.8x | | k+1=18 | | 5x+25=99 | | p(x)=-x^2+34x+29 | | 2x-13=-3x-3 | | 3x^3-75x^3= | | 4(6t+1)-16=t-(t+11) | | 37d^2-40d=0 | | 3x-14+x=x-23 | | (y-3)-(y-5)-7= | | -6r+2(r+2)=-20 | | 3x^3-75x^3=0 | | 2=n+0.8 | | 4m^2+3m+18=9 | | 7x+49=6x+2 | | 2.3x+35.2=13.0-8.8x | | x^4x^3/x^5 | | swag=2 | | 2x-2=5x+10 | | 0.5(x+90)+1.3x=26 | | 2^4(x^9)/2^7(x^4) | | findmy=mx+b | | 7x+14=6x+24 | | 7(z+6)=7(z-3) | | 0=w^2-4w | | 3b-2=76+4 | | 7/8(w+1)+5/6(w-3)= |

Equations solver categories